2022
DOI: 10.3390/plants11070933
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Protein Trafficking: A New Player in Low-Temperature Response Pathway

Abstract: Unlike animals, plants are unable to escape unfavorable conditions, such as extremities of temperature. Among abiotic variables, the temperature is notableas it affects plants from the molecular to the organismal level. Because of global warming, understanding temperature effects on plants is salient today and should be focused not only on rising temperature but also greater variability in temperature that is now besetting the world’s natural and agricultural ecosystems. Among the temperature stresses, low-tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 120 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…It has been widely reported, in order to reveal the preparation of the cold acclimation mechanisms, great attention should be paid to changes in membranes and their functions [ 11 , 13 , 14 , 56 ]. However, while it is recognized that proteins are key structural and functional elements within the cell, such as structural components of membranes, transporters, enzymes, and receptors, influencing and determining a variety of metabolic processes within the cell, including growth and development processes and cold resistance [ 57 , 58 , 59 , 60 ], till now, their metabolic processes, compositional changes, and relationships with plant resistance and preparation for wintering have not been fully investigated and disclosed. Experiments, especially on herbaceous plants, are usually carried out by simulating the process of cold acclimation, i.e., by changing the temperature and the duration of the photoperiod under control conditions [ 29 , 47 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely reported, in order to reveal the preparation of the cold acclimation mechanisms, great attention should be paid to changes in membranes and their functions [ 11 , 13 , 14 , 56 ]. However, while it is recognized that proteins are key structural and functional elements within the cell, such as structural components of membranes, transporters, enzymes, and receptors, influencing and determining a variety of metabolic processes within the cell, including growth and development processes and cold resistance [ 57 , 58 , 59 , 60 ], till now, their metabolic processes, compositional changes, and relationships with plant resistance and preparation for wintering have not been fully investigated and disclosed. Experiments, especially on herbaceous plants, are usually carried out by simulating the process of cold acclimation, i.e., by changing the temperature and the duration of the photoperiod under control conditions [ 29 , 47 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…It had been reported that changes in the protein composition from the cell membranes during the period of cold acclimation in the organs which are important for wintering in herbaceous plants (the terminal bud and root collar) need to be analyzed due to changes in the condition and functional properties of membranes [ 11 , 56 , 68 ]. In addition, proteins from the cell membrane are essential for the study of phytohormones and their interaction with receptors [ 57 , 60 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plants participate in cold stress response through ICE-CBF regulatory pathway (Ashraf et al 2022). Under cold and other abiotic stresses, CYSb is produced and takes part in the DREB and AREB signal transduction pathways (Zhang et al, 2008).…”
Section: Co-application Ofmentioning
confidence: 99%
“…ABA (abscisic acid), JA (jasmonic acid), SA (salicylic acid), BR (brassinosteroid), and ET (ethylene) are involved in the plant response to cold stress by impacting CBF either individually or in combination. In contrast, the effects of Auxin and CK (cytokinin) are attributed to the modulation of hormone transporters under cold stress conditions, consequently impacting concentration gradients [16,17]. Moreover, downstream gene activation can be directly triggered by HY5 (enhanced hypocotyl 5), REV4 (reville4), REV8 (reville8), and CCA1 (circular clock associated 1) without the involvement of the CBF pathway [18,19].…”
Section: Introductionmentioning
confidence: 99%